Pengaruh Lingkungan Kerja terhadap Kinerja Perangkat Nagari dalam Pengelolaan Keuangan Nagari di Kabupaten Tanah Datar - Nur Putri Jayanti; Syamsir Syamsir (Journal of Education on Social Science (JESS), 2018)
Law No. 6/2014 stated that the Village Government should be able to perform the task of managing village finances with a large budget and to provide accountability for the expenditure. The problems that occurred in Tanah Datar were that the nagari treasurers were less transparent about the nagari's financial management. The purpose of this study was to analyze the influence of work environment on the performance of nagari apparatus in managing nagari finance. This study used quantitative method. The population in this study consisted of 525 respondents and 227 of them were chosen as sample determined with Slovin formula and proportional random sampling technique. The data were analyzed with linear regression. The result of this study indicated that simultaneously and partially the work environment had significant effects on the performance of the nagari apparatus in the management of nagari finance in Tanah Datar District.